(untitled) (Alternautas, 2023)
This paper explores how the right to the city is understood and practiced in relation to public space by contrasting two models of urban planning in Bogotá, Colombia. It contrasts a best practice right to the city/public space model with an alternative vision for urban ordering based on participatory forms of living heritage. I argue that this represents a kind of insurgent heritage that offers a potentially rich and powerful concept for extending the right to the city to further push for including alternative worldviews and practices in planning and policymaking. To develop this argument, I discuss theories related to public space, the right to the city, and critical heritage. I then use these to discuss an ethnographic study of heritage planning in the Traditional Center of Bogotá.